Effect of Scrotal Insulation on Semen Quality Profiles in Mithun - Perumal, P. (International Journal of Bio-resource and Stress Management, 2018)
Testes are highly sensitive to increasing body or scrotal temperature or thermal insulation of testis which in turn causes degenerative changes causes reduction of testicular weight and size as well as alteration in its consistency, which ultimately leads to deleterious effects on semen production and its quality profiles. The present study was conducted to assess the adverse effects of scrotal insulation on semen quality profiles (SQPs), seminal antioxidant profile (total antioxidant capacity; TAC) and oxidative stress (malondialdehyde; MDA) in mithun bulls. The study was conducted in livestock farm, ICAR-National Research Centre on Mithun, Medziphema, Nagaland, India. Semen ejaculates were collected twice a week from six adult healthy mithun bulls with good body condition score (5–6) from day of scrotal insulation (day 0) to day 42 of post insulation to know the effect of scrotal insulation on SQPs, TAC and MDA of mithun semen. Scrotal insulation was applied for 5 days (day 0: day of insulation). Semen ejaculates were collected & evaluated upto the day 42 of experimental period. Result revealed that scrotal insulation has significant (p<0.05) effect on the SQPs, TAC and MDA upto day 42 of insulation. However, these scrotal insulated animals were recovered gradually in SQPs as well as antioxidant profiles. The adverse effects of scrotal insulation on SQPs, TAC and MDA indicated that the semen collection as well as preservation required to be suspended till day 42 of scrotal insulation to get good quality or normal semen to avoid the conception failure in artificial insemination (AI) centre using such semen in mithun.